The picture atlas An incredible journey - "Holland, Simon"; Galder, Jill (Illustrator) (Bloomsbury childrens: Great Britain, 2017)
Explore the world by looking not only at borders, mountains, rivers, seas and oceans, but by discovering the natural wonders of the world, historical artefacts, amazing animals, fascinating cultures and much much more. With stunning illustrations from the incredible Jill Calder, The Picture Atlas is quite unlike anything you've seen before. From the freezing Arctic Circle with its powerful orca whales, to the amazing Sydney Opera House and the Great Barrier Reef, learn, explore and be amazed by the wonders of the world.Bursting full of beautiful artwork, informative maps and astounding facts, take a trip around the world like you've never seen it before.
Keywords: Atlas